Influence of cage or pen housing on carcass traits and meat quality of rabbit - S. Combes (Animal, 2010)
Carcass traits and meat quality of rabbits reared in conventional cages (0.385 m2), small pens (0.662 m2) or large pens (4.052 m2) at a similar stock density of 15 rabbits/m2 were compared (n = 30 per group). Pens contained an elevated platform. Slaughter weight (SW; P < 0.01) and cold carcass weight (P < 0.05) decreased in the order of Cage < Small pen < Large pen groups. SW and cold carcass weight were 7% lower in rabbits housed in large pens than in cages. Dressing out and meat-to-bone ratio were not influenced by the housing system. Percentage of fat deposits was highest in caged rabbits (+0.15 point for scapular fat and +0.26 point for perirenal fat compared to rabbits reared in large pens P < 0.05). Rabbits housed in large pens had a bigger proportion of hind part (+1 point), and meat colour was shifted towards greater a* values (P < 0.01) compared to caged rabbits. Water holding capacity and shear test parameters in longissimus lumborum muscle, lipid content and shear test parameters of abductor cruralis cranialis, biceps femoris and semitendinosus muscles were not affected by the housing system. Tibia and femur bone moment of inertia increased in the order of Cage < Small pen < Large pen groups (P < 0.05), whereas elastic modulus, which is a measure of intrinsic stiffness, was highest in caged rabbits. This study showed that large pen housing altered carcass traits independently and increased meat redness and fracture resistance of tibia and femur.